2020
DOI: 10.1155/2020/8617430
|View full text |Cite
|
Sign up to set email alerts
|

Feature Selection Using Genetic Algorithms for the Generation of a Recognition and Classification of Children Activities Model Using Environmental Sound

Abstract: In the area of recognition and classification of children activities, numerous works have been proposed that make use of different data sources. In most of them, sensors embedded in children’s garments are used. In this work, the use of environmental sound data is proposed to generate a recognition and classification of children activities model through automatic learning techniques, optimized for application on mobile devices. Initially, the use of a genetic algorithm for a feature selection is presented, red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 46 publications
0
17
0
2
Order By: Relevance
“…For feature selection through genetic algorithms, we used the genetic Galgo algorithm [37] and the random forest classifier algorithm [38], which demonstrated superior accuracy to the algorithms k-nearest neighbor, nearest centroid, artificial neural networks and recursive partition trees in our previous work of feature selection, using genetic algorithms applied to children's activity classification using environmental sound [17].…”
Section: Genetic Algorithmsmentioning
confidence: 99%
“…For feature selection through genetic algorithms, we used the genetic Galgo algorithm [37] and the random forest classifier algorithm [38], which demonstrated superior accuracy to the algorithms k-nearest neighbor, nearest centroid, artificial neural networks and recursive partition trees in our previous work of feature selection, using genetic algorithms applied to children's activity classification using environmental sound [17].…”
Section: Genetic Algorithmsmentioning
confidence: 99%
“…Dominguez et al [33] utilize GA for feature selection to reduce the original size of the environmental sound data. Liu et al [34] propose a fast wrapper feature subset selection algorithm based on PSO, which employs the domain knowledge of feature subset selection problems.…”
Section: Related Workmentioning
confidence: 99%
“…Genetic algorithms (GAs) have been previously used for feature selection and showed significant results for selecting the best feature sets [24,25]. In the health arena, GA can highly improve the performance of models for emotional stress state detection [26], severe chronic disorders of consciousness prediction [27], children's activity recognition and classification [28], gene encoder [29], hepatitis prediction [30], and COVID-19 patient detection [31].…”
Section: Genetic Algorithm (Ga)mentioning
confidence: 99%
“…Feature selection is used to reduce the dimensionality of data [20,21] and in medical diagnosis, is used to identify most significant features related to disease [22,23]. Genetic algorithm (GA) is a feature selection method that has been used to find the best feature subsets [24,25] and shown significant advantage for improving the performance of emotional stress state detection [26], severe chronic disorders of consciousness prediction [27], children's activities regarding recognition and classification [28], gene encoder [29], hepatitis prediction [30], and coronavirus disease (COVID-19) patient detection [31]. A previous study revealed that a combination of GA and XGBoost has improved the model performance [32].…”
Section: Introductionmentioning
confidence: 99%